Examine the Multifaceted role of police in Preventing Child offending through Proactive Measures (Journal of Advances and Scholarly Researches in Allied Education, 2023)
"Crime prevention" means "strategies and measures that try to lower the risk of crimes happening and their possible negative effects on people and society, such as fear of crime, by stepping in to change their many causes."1 The best way to lower crime numbers, especially crimes made by children, is to stop them from happening in the first place. Children should not be able to commit crimes because it is good for them, their families, their neighborhoods, and society as a whole. A number of international documents that deal with children include rules for keeping kids from committing crimes. The UN Guidelines for the Prevention of Juvenile Delinquency (1990), which are also known as the "Riyadh Guidelines," are all about keeping kids from breaking the law. About 100 years ago, the United States set up a different system for juvenile justice. Its goal was to keep young convicts out of the harmful hands of criminal courts and to help them get better by focusing on each individual's needs.